The objectives and references of Mi‘yar al-‘Ilm fi Fann al-Mantiq - Towpek, Yaman; Kamaruddin Salleh (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
Mi‘yar al-‘Ilm fi Fann al-Mantiq of al-Ghazali is the first book written specifically on Muslim logic. But the comprehensive and exclusive study on the essence of its scientific contents of the book and its significance in developing scientific thinking has never been done. Thus this study investigates the objectives and referral sources of Mi‘yar writing. This qualitative study uses content analysis method. The data which were collected using the documentation has been analyzed using the inductive, deductive, and comparative methods. The process of analysis of logic in Mi‘yar be done using textual analysis or textual content analysis and constant comparison method. It is because of this study is a textual study. This study found that Mi‘yar written by two objectives. Firstly; to provide an understanding on the methodologies of thinking and researching, and explain the rules of constructing syllogisms and analogies. Secondly; to review the matters which have been written in Tahafut. The study also found that al-Ghazali wrote Mi‘yar based on three books, a book of his own, namely Maqasid, and two books of Ibn Sina, namely al-Isharat and al-Risalah fi al-Hudud. Therefore Mi‘yar should be a fundamental source of learning logic and methods of thinking of Muslims either at high school or university. Hence the constant and deep study on the content of Mi‘yar is very significant and has high impact. But the dissemination of the findings of this study is the next action that should be realized.